Silvicultura Intensiva: innovación forestal para un futuro sostenible Un grupo de investigación del TEC que impulsa la productividad forestal en Costa Rica - Guevara-Bonilla, Mario (2026)
Intensive forestry is seen as the country’s strategy to maximize the productivity of our forest plantations and consequently meet the demand for high-quality wood. With this vision in mind, the Intensive Forestry Research Group was created in 2020 at the TEC School of Forestry Engineering. Using a multidisciplinary approach, the group aims to provide tools that allow producers, technicians, and decision-makers in the forestry sector to increase the productivity of forest plantations and offer a quality product for the national and international markets. Below is a summary of the creation of the Intensive Forestry Research Group, its achievements, and future expectations.